Transarterial chemoembolization with 125I seed insertion for multifocal hepatocellular carcinoma - Wang, You-Bin; Zhang, Ying; Li, Peng-Fei; Bao, Le; Zhang, Wen-Tao (Frontiers in Oncology, 2024)
Background: A common treatment strategy for individuals with multifocal hepatocellular carcinoma (HCC) who are not candidates for surgical resection is transarterial chemoembolization (TACE). Combining TACE with 125I seed insertion (ISI) may offer a means of enhancing therapeutic efficacy. The purpose of this study was to compare the therapeutic efficacy of TACE administered with and without ISI for the treatment of multifocal HCC. Methods: The data from the two centers were analyzed retrospectively. The present study involved 85 consecutive patients with multifocal HCC who underwent TACE between January 2018 and December 2021. Of these patients, 43 were in the combined group, receiving TACE with ISI, and 42 were in the TACE-only group, receiving TACE without ISI. Comparisons of treatment outcomes were made between these groups. Results: No significant differences in baseline data were observed between these groups of patients. Higher rates of complete (60.5% vs. 33.3%, P = 0.016) and total (93.0% vs. 61.9%, P = 0.001) responses were evident in the combined group compared to the TACE-only group. Median progression-free survival (PFS, 13 vs. 10 months, P = 0.014) and overall survival (OS, 22 vs. 17 months, P = 0.035) were also significantly longer in the combined group than in the TACE-only group. Using a Cox regression analysis, risk variables associated with shorter PFS and OS included Child-Pugh B status (P = 0.027 and 0.004) and only TACE treatment (P = 0.011 and 0.022). Conclusions: In summary, these findings suggest that, as compared to TACE alone, combining TACE and ISI can enhance HCC patients' treatment outcomes and survival.